The great trade collapse and the Spanish export miracle: Firm-level evidence from the crisis - Peter S. Eppinger; Nicole Meythaler; Marc-Manuel Sindlinger; Marcel Smolka (University of Tübingen, Faculty of Economics and Social Sciences, 2016)
We provide novel evidence on the micro-structure of international trade during the 2008 financial crisis and subsequent global recession by exploring a rich firm-level data set from Spain. The focus of our analysis is on changes at the extensive and intensive firm-level margins of trade, as well as on performance differences (jobs, productivity, and firm survival) across firms that differ in their export status. We find no adverse effects of the financial crisis on foreign market entry or exit, but a considerable increase in the export intensity of firms after the financial crisis. Moreover, we find that exporters were more resilient to the crisis than non-exporters. Finally, while exporters showed a significantly more favorable development of total factor productivity after 2009 than non-exporters, aggregate productivity declined substantially in a large number of industries in Spanish manufacturing. We also briefly explore two factors that might help explain the surprisingly strong export performance of Spain in the aftermath of the great trade collapse: improved aggregate competitiveness due to internal and external devaluation and a substitutive relationship between domestic and foreign sales at the firm level.
urn:nbn:de:bsz:21-dspace-739394
Keywords: F10; F14; G01; D24; 330; international trade; financial crisis; Spain; manufacturing; firm-level data